W sprawie wykonywania zakazu prowadzenia pojazdów w ruchu drogowym - Łucarz, Katarzyna (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
The topic of this analysis is the enforcement problem related to a ban on driving motor vehicles. After a short historical outline of the problem, the majority of this analysis concerns the current regulations in this regard. By presenting, in detail, the enforcement proceedings of this penalty, the author touches upon subjects relating to, among others: defining the appropriate enforcement agencies, the scope of their actions and, finally, establishment of a minimum critical point which initiates judicial proceedings.
Keywords: zakaz prowadzenia pojazdów mechanicznych; prawo jazdy; cofnięcie uprawnienia do kierowania pojazdami; prawny bieg zakazu prowadzenia pojazdów mechanicznych; postępowanie egzekucyjne